Pengaruh Penerapan Pembelajaran Daring Dalam Meningkatkan Hasil Belajar Bahasa Inggris Materi Recount Text - Dwi Martiani (BRIGHT : A Journal of English Language Teaching, Linguistics and Literature, 2021)
The purpose of this study was to determine whether there was a student response and the effect of the application of online learning in improving English learning outcomes on Recount text material in class X MIPA 4 SMA Negeri 1 Boyolangu. This type of research is a classroom action research conducted online via Zoom and Google Classroom. The subjects in the study were students of class X MIPA 4 at SMA Negeri  1 Boyolangu  in the even semester of the 2020/2021 academic year, and the object of this study was to understand the recount text material and student responses to online learning. This study uses two cycles to improve the ability to analyze recount text through four stages of the activity process which includes: planning, action, observation, evaluation and reflection. Data collection techniques in this study are using test and observation methods. The results showed (1) the application of online learning can improve students' understanding of recount text material. (2) there is a student response to the application of online learning to improve students' understanding of recount text material.